2014
DOI: 10.3892/etm.2014.1700
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Xin Mai Jia ultrafiltration extract on human umbilical vein endothelial cell injury induced by hydrogen peroxide and the effect on the NO-cGMP signaling pathway

Abstract: The aim of the present study was to evaluate the protective effect of the ultrafiltration extract of Xin Mai Jia (XMJ) on a human umbilical vein endothelial cell (HUVEC) injury model induced by hydrogen peroxide (H2O2), by providing experimental data to investigate the mechanism and efficacy underlying the therapeutic effects on atherosclerosis. HUVECs were first injured by H2O2 and then varying final concentrations of the Chinese herb extract were added. Effects of the XMJ extract on morphology, activity, mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…1D and E , incubation of HUVECs with H 2 O 2 dramatically reduced NO productions and damaged cell viabilities. However, XMJ concentration-dependently reversed NO generations and cell proliferations, consistent with our previous report 19 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1D and E , incubation of HUVECs with H 2 O 2 dramatically reduced NO productions and damaged cell viabilities. However, XMJ concentration-dependently reversed NO generations and cell proliferations, consistent with our previous report 19 .…”
Section: Resultssupporting
confidence: 93%
“…By using gene expression array, we identified several signaling pathways related to NO, FOXO, apoptosis, cell cycle, AMPK, MAPK, NF-kB, and PPAR, which were affected by XMJ in endothelial cells. We choose NO signaling as a candidate because NO signaling was in the pecking order among these signaling, consistent with our previous studies that XMJ produces the anti-inflammatory and antioxidant effects in HUVECs by increasing NO productions 19 26 27 . This is also highly related to clinical investigations that Chinese medicine has globally recognized to improve health conditions by activating NO signaling 28 .…”
Section: Discussionmentioning
confidence: 91%
“…Excessive levels of ROS in endothelial cells leads to impaired endothelial nitric oxide (NO) bioactivity (7,8). NO, a type of vasodilator, is secreted by endothelial cells, and 30% of blood NO levels are produced by endothelial nitric oxide synthase (9). Previous studies have reported that increased ROS generation in endothelial cells contributes to their dysfunction in hypertension (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 10 11 12 ] The previous studies of our group showed that Gegen and its TCM preparation XinMaiJia could effectively inhibit the occurrence and development of atherosclerosis. [ 13 14 15 16 ]…”
Section: Introductionmentioning
confidence: 99%